The Effect of Alcoholic Extracts of Zingiberofficinale Anti-E.Coli Isolates Isolated from Urinary Tract Infection - Mohammed, luma Saeed (Iraqi Journal of Science, 2019)
The Escherichia coli isolated from UTIs, were identified with biochemical tests and vitek test.The ethanolic extracts of Zingiberofficinale(Z.officinale) were tested against E.coli by using the good agar diffusion test, the alcoholic extracts from (25 -100) mg/ml showed antimicrobial activity against tested microorganism. The diameter of inhibition zone increase at high concentrations and rang from (18-20mm) , and these results compared with antibiotics sensitivity discs were used by discs diffusion method against E.coliisolates, they were resisted to all antibiotics used in this study. It could be concluded that alcoholic extract of Z.officinalehad good antimicrobial effects, and may be able to use for treatment UTIs caused by E.coli because it not make any side effect and can be used occasionally to prevent the infect by this bacteria.